The Reproductive Transition in an Indigenous Population of Northern Argentina - Lanza, Norberto (2013)
Latin America has been registering a fast decrease in fertility rates since the mid-twentieth century. This change can be linked to the modernization process these populations have been undergoing. However, research with Latin American indigenous populations, which are undergoing relatively similar lifestyle changes, shows very different trends in fertility. The aim of this study was to analyze fertility patterns in the indigenous Toba community of Cacique Sombrero Negro, which is experiencing a rapid process of economic and social Westernization. Fertility patterns were analyzed between 1981 and 1999, the period for which the most accurate records were found. Results showed an overall increase in fertility rates and changes in the age of peak fertility across time periods. It is hypothesized that the lifestyle transition this population is experiencing leads to better access to resources that, in the absence of contraception, allow for a higher number of offspring. Nevertheless, this higher resource availability would be differential, affecting mostly the fertility of younger mothers.